2021
DOI: 10.1186/s12885-021-08030-0
|View full text |Cite
|
Sign up to set email alerts
|

An energy metabolism-based eight-gene signature correlates with the clinical outcome of esophagus carcinoma

Abstract: Background The essence of energy metabolism has spread to the field of esophageal cancer (ESC) cells. Herein, we tried to develop a prognostic prediction model for patients with ESC based on the expression profiles of energy metabolism associated genes. Materials and methods The overall survival (OS) predictive gene signature was developed, internally and externally validated based on ESC datasets including The Cancer Genome Atlas (TCGA), GSE54993 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…This process was performed based on R package “survcomp”. In addition, we used restricted mean survival time (RMST) curves to evaluate the performance of each model and compare their differences ( Schröder et al, 2011 ; Zheng et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This process was performed based on R package “survcomp”. In addition, we used restricted mean survival time (RMST) curves to evaluate the performance of each model and compare their differences ( Schröder et al, 2011 ; Zheng et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we found that the amplification of ZBTB6 was related to a high risk of LNM. There have been few studies of ZBTB6, a gene related to energy metabolism, and it has only been reported to be a prognostic indicator in esophageal cancer (27). Here, we found that the amplification of ZBTB6 was related to a high risk of LNM in TNBC, but the mechanism is still unknown.…”
Section: Discussionmentioning
confidence: 64%
“…Consequently, exploiting novel prognostic indicators and therapeutic approaches is particularly crucial. Numerous researchers have made efforts on biomarker-based classifier and obtained encouraging achievements in assessing the survival outcome of EC [ 22 , 23 ]. Nevertheless, these prognostic models are more or less flawed and we need to discover more powerful signature for prognosis prediction.…”
Section: Discussionmentioning
confidence: 99%